ASUHAN KEBIDANAN PADA IBU NIFAS Ny ”A” P2A0H2 DI KLINIK UTAMA NILAM SARI TEMBILAHAN TAHUN 2019 - Laylis Shofyati; Nurul Indah Sari (Jurnal Kesehatan Husada Gemilang, 2021)
The postpartum period is a period that starts from 2 hours after the birth of the placenta up to 6 weeks after that. The most important thing in the puerperium is the evaluation of the occurrence of bleeding, because postpartum bleeding can cause postpartum maternal death. Complete postpartum coverage in Indragiri Hilir was 73.5%. Data on postpartum mothers at the Nilam Sari Tembilahan Main Clinic in 2019 as many as 124 people. The care is held from June 24 to August 03, 2019. The purpose of midwifery care is to be able to provide midwifery care to Mrs. "A" P2A0H2 as postpartum mothers. The method of data collection using varney's thought flow midwifery upbringing management is documented in SOAP form. The results of the care were obtained after it was done 3 times. First visit in 8 hours postpartum. The second visit on 6 days postpartum and the third visit on 40 days postpartum by conducting assessment, interpretation, identification of diagnoses or potential problems, immediate action, care plan, implementation, evaluation and analysis of gaps between theory and practice. The conclusion found there is a gap between theory and practice about the administration of drugs in the postpartum period. The main clinical advice of nilam sari is to apply obstetric care in the place of practice in accordance with the standard procedures that have been established, namely to make nifas visits 3 times and minimize the occurrence of gaps between theory and practice.